Značaj kognitivnog opterećenja kod procene obmanjujućeg ponašanja - Baić, Valentina; Ivanović, Zvonimir M.; Veljković, Milan (NBP. Nauka, bezbednost, policija, 2021)
Abstract: The paper presents research aimed at examining the significance of increased cognitive load on the generation of verbal and vocal signs in false and true expressions. The results of previous research indicate the importance of this concept in the assessment of lying. The research involved 100 respondents (47 men and 53 women), students of the master’s studies of criminalistics at the University of Criminal Investigation and Police Studies, aged 23-44. Respondents had the task, based on the observation of twenty carefully selected videos (10 true statements and 10 false statements), to mark the frequency of each individual verbal and vocal sign, on a previously generated and prepared list. The results show that there is a statistically significant difference in terms of the frequency of all verbal and vocal signs in a false or true statement: response latency (Z = -3.931, p = 0.000), speech hesitation (p = 0.000), speech errors (p = 0.000)), speech rate (Z = -3.921, p = 0.000), number of spoken words in the utterance (Z = -3.921, p = 0.000) and length of utterance (Z = -3.923, p = 0.000). Response latency, speech hesitation, and speech errors have higher median values ​​in false utterances than in true ones, while speech rate, number of words spoken, and length of utterance show higher median values ​​in true than false utterances.